Trajectory control of redundant manipulators - Tenreiro Machado, J. A. (1997)
This paper presents the fundamental aspects of the theory of the generalized matrices and explore their application on the control of redundant manipulators. Redundant manipulators have some advantages when compared to classical arms because they allow a trajectory optimization, both on the free space and on the presence of obstacles, and the resolution of singularities. Nevertheless, for this type of manipulators the kinematic control adopts algorithms that use generalized inverses matrices. Consequently, the concepts associated with the control by generalized inverses are tested through several experiments that reveal the difficulties that often arise. In this perspective, it is studied the control of redundant and hybrid-redundant manipulators namely through the analysis in points of singularity, showing that we may get non-optimal arm configurations.